Scaffolding Practices in English Writing Instruction of Senior High School Teachers - Ognase, Eloisa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study thoughtfully examined the scaffolding practices employed by Senior High School English teachers in teaching writing in Kayapa, Nueva Vizcaya. Specifically, it explored the scaffolding strategies utilized by teachers, the challenges they encountered during implementation, and the interventions they employed to address students’ writing difficulties. The study employed a qualitative descriptive research design, involving Senior High School English teachers as respondents. Data were gathered through semi-structured interviews and classroom observations to obtain detailed information regarding actual classroom practices and teacher experiences. The findings revealed that teachers commonly employed scaffolding strategies such as building the field, modeling, joint construction, independent writing, peer tutoring, and instructional materials to support students’ writing development. These practices were instrumental in enhancing students’ confidence, participation, collaboration, and understanding of writing tasks. However, teachers faced several challenges, including limited vocabulary, grammar difficulties, varying student abilities, low motivation, off-task behavior, and time constraints. To address these concerns, teachers employed interventions such as continuous feedback, collaborative learning, rewards, motivational activities, dictionary use, and peer assistance. The study concluded that scaffolding practices play a significant role in enhancing students’ English writing skills and engagement in classroom activities. Furthermore, the findings highlight the importance of guided instruction, collaborative learning, and supportive teaching strategies in improving writing proficiency among Senior High School learners.